Análise da inserção e funcionamento de uma usina solar na UFERSA – Campus Caraúbas - Santos, Ítalo Grangeiro (Universidade Federal Rural do Semi-Árido, 2018)
The use of electricity is essential in modern society and therefore it is essential to be produced on a large scale. Due to the major water crisis and the consequent increase in fare prices, engineers are opting for sustainable civilian buildings, such as the deployment of photovoltaic energy. This energy is the result of the transformation of sunlight into electric current. The objective of this study is to verify the feasibility of insertion and operation of a solar power plant at UFERSA - Campus Caraúbas. This field study was a descriptive approach. It was considered the period of twelve months, from December 2016 to November 2017. The tool used was a solar simulator and the budgetof the cost of implantation of the photovoltaic system was made. A comparison was made between significant differences between electric and photovoltaic systems, with the cost of setting up a photovoltaic power plant for R $ 208,500.00. From the results found it becomes remarkable that the installation of a photovoltaic system in place is feasible. Among the positive points was the reduction of CO2 emissions, avoiding around 158,041 kg/a, reducing the environmental or social impact. Among the negative points is the non-generation of energy during the night, therefore, it should generate more costs in the storage of energy by means of batteries. It is suggested the investment for the insertion and operation of a solar plant at UFERSA – Campus Caraúbas, to be used in addition, clean, and inexhaustible, sources that do not harm the environment, protecting future nations.
Monografia
Keywords: Energia fotovoltaica; Energia solar; Viabilidade; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA